Analisis Penyebab Diselenggarakannya Pemungutan Suara Ulang (PSU) Di Provinsi Jawa Timur Tahun 2024 - Irsyedha Alfara Reginantis; Nadiah Aurahmadani Priyambodo; Adam Jamal (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The research that we conducted has the aim of knowing the causes of the Re-voting (PSU) ini the 2024 simultaneous general elections in East Java. Aiming to see what factors are behind the PSU. This research was conducted to see the decisions making carried out by Bawaslu in handling allegations of fraud that occurd during the 2024 election process. With the aim of knowing the process in making decisions for organizing  PSUs. The method used is qualitative with a literature study approach to collect data to conduct in-depth alaysis which is then presented in the form of a literacy that is useful for adding information to readers and can also be used to make considerations in every decision-making process when facing a problem. The emergence considerations in the form of re-voting is mentioned when a whole process of analyzing various reports, information and data obtained by the Regional Election Supervisory Committee has been carried out. The report willlater be used as basic evidence related to all findings of fraud in the implementation of elections that violate laws and regulations. So that information about the occurrence of these violations will be the cause behind the PSU based on Article 372 paragraphs (2) of Law Number 7 Year 2017 cencerning elections. Things like this should be prevented trough actions that have been taken by the government long before the implementation of the 2024 elections and supported by the organizing committee and election participants can understand the rules regarding the implementation of voting until the time the vote count is carried out.